Strengthening gender justice in a just transition: A research agenda based on a systematic map of gender in coal transitions - Paula Walk; Isabell Braunger; Josephine Semb; Carolin Brodtmann; Pao-Yu Oei; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
For climate change mitigation a rapid phase-out of fossil fuels such as coal is necessary. This has far-reaching gender-specific consequences. This paper presents a systematic map of the literature that examines the impact of historical coal phase-out processes on women and their role in these processes. The search process consists of screening 2,816 abstracts and reading 247 full-text studies. The analysis of the 73 publications ultimately included in the systematic map shows that past coal phase-outs meant, both opportunities (e.g. increased labour market participation) as well as burdens for women (e.g. double burden of job and household). It becomes clear that agency within coal transitions was also gendered. For example, it was difficult for women to gain access to union structures, which led them to organise themselves into grassroots movements. Our research shows that policies aiming for a just sustainability transition should always be explicitly gender-responsive. However, the impact of sustainability transitions on women's lives remains largely under-researched. Therefore, we propose a research agenda based on our findings containing six key issues that need to be addressed scientifically.
Keywords: O13; Q52; B54; 330; Gender; Coal Phase-Out; Just Transition; Systematic Map